G189(P) The use of simulation to teach medical students how to recognise and manage a sick child – a cluster randomised trial. (27th April 2015) - Harnik, E; Mackay, K; Jacob, H; Morrissey, B; Moreiras, J
Abstract : Aims: Many medical students lack confidence in their ability to recognise and manage acutely unwell patients, particularly children. With less time available for training and reduced exposure to sick children, simulation is being used effectively to develop technical and non-technical skills in postgraduate paediatric training. Our aim was to evaluate the impact of a one-day paediatric simulation course on medical students' self-reported ability and confidence in recognising and managing sick children. Method: We conducted a cluster-randomised study of the impact of a novel undergraduate paediatric simulation course. All students undertaking their paediatric placement at a district general hospital over a six month period were invited to take part. Students were cluster randomised into the intervention (simulation) group or control group (standard paediatric attachment). Students in the intervention group attended a one-day simulation course during the last week of their attachment. The course included clinical skills stations, a discussion on human factors, and five simulations of common paediatric emergencies, each followed by a structured debrief. All participants completed a questionnaire at the end of their attachment and those in the intervention completed a further questionnaire after the simulation day. The primary outcome measure was students' self-reported ability and confidence in recognising, assessing and managing sick children. The secondary outcome measured was their views on the course. Results: Sixty one students participated: 32 in the intervention group and 29 in the control group. Self-assessed confidence in recognising a sick child was higher after the simulation course compared to controls (difference in confidence 0.75/5, 95% CI 0.40–1.10, p = 0.0002). Similarly, those in the intervention group were more confident in assessing and managing a sick child (difference in confidence 1.02/5, 95% CI 0.74–1.31, p < 0.0001). Six key themes were identified from the qualitative responses, including increased confidence in emergency situations and an appreciation of human factors. Students found the simulation useful and wanted it offered to all undergraduates during child health attachments. Conclusion: A one-day simulation course improves medical students' confidence in assessing and managing unwell children and is highly valued by students. Further studies are needed to evaluate its impact on clinical performance and confidence over time.